PET/CT in Thyroid Cancer (PET/CT,, 2018)
This pocket book provides a comprehensive review of the current use of PET/CT in thyroid cancer, offering a multidisciplinary perspective and explaining the role of PET/CT in relation to other imaging modalities. A key aim is to help readers to choose the correct imaging modality to answer the clinical question at hand, thereby assisting in patient management. Highlights of the book include the exquisite depiction of normal variants, pitfalls, and artifacts and a pictorial atlas of the types of thyroid cancer and their imaging appearances. Readers will also find helpful information on the relation of the clinical and pathological background to imaging. The book will be an excellent asset for practitioners and trainees in Nuclear Medicine and members of endocrine and oncology teams. It is published within the Springer series Clinicians' Guides to Radionuclide Hybrid Imaging, in which leading professionals succinctly explain the importance of nuclear medicine in the diagnosis and management of oncological and non-oncological conditions.